Gamification and reputation - Aparicio, Manuela (2021)
Aparicio, M., Costa, C. J., & Moises, R. (2021). Gamification and reputation: key determinants of e-commerce usage and repurchase intention. Heliyon, 7(3), [e06383]. https://doi.org/10.1016/j.heliyon.2021.e06383